Structure dependent electrochemical performance of Li-rich layered oxides in lithium-ion batteries. (May 2017) - Fu, Fang; Yao, Yuze; Wang, Haiyan; Xu, Gui-Liang; Amine, Khalil; Sun, Shi-Gang; Shao, Minhua
Abstract: Rational and precise control of the structure and dimension of electrode materials is an efficient way to improve their electrochemical performance. In this work, solvothermal or co-precipitation method is used to synthesize lithium-rich layered oxide materials of Li1.2 Mn0.56 Co0.12 Ni0.12 O2 (LLO) with various morphologies and structures, including microspheres, microrods, nanoplates, and irregular nanoparticles. These materials exhibit strong structure-dependent electrochemical properties. The porous hierarchical structured LLO microrods exhibit the best performance, delivering a discharge capacity of 264.6 mAh g −1 at 0.5 C with over 91% retention after 100 cycles. At a high rate of 5 C, a high discharge capacity of 173.6 mAh g −1 can be achieved. This work reveals the relationship between the morphologies and electrochemical properties of LLO cathode materials, and provides a feasible approach to fabricating robust and high-performance electrode materials for lithium-ion batteries. Graphical abstract: Highlights: Microsphere, microrod, nanoplate, and irregular structured Li1.2 Mn0.56 Co0.12 Ni0.12 O2 (LLO) are synthesized. The relationship between the morphologies and electrochemical properties of LLO are investigated. Porous LLO microrods exhibit the best performance. The prominent performance of LLO microrods arises from the synergistic effect of 1D shape and porous hierarchical structure.